THE IMPACT OF PERSONAL MATURITY ON FAMILY STABILITY - Aleksanyan, Anna (Modern Psychology, 2025)
This article discusses the impact of psychological traits and personal maturity on family stability. The family, being the most significant institution in society, is where a person’s identity is formed and developed. The influence of the family on the development of personal identity is immense, especially in the context of communication dynamics and parenting styles, which shape individual behavior, emotional health, and psychological well-being. These, in turn, are crucial factors for forming a stable and strong family.Family stability is greatly influenced by the social environment, economic factors, and the cultural characteristics of society. A key role in building harmonious and stable family relationships is played by personal maturity, which is a lifelong, ongoing process of self-development. One component of personal maturity is considered to be a person's ability to form and live within a family. Many psychologists argue that family stability, as a problem, depends on the ability to overcome cohabitation challenges, and in this context, the issue of individual maturity is often overlooked. There arises a need to determine how personal maturity and family relationships are interconnected and what patterns they follow.A study was conducted on the psychological maturity and personal traits of individuals who have been married for a long time and those who are divorced. This research made it possible to identify key components of personal maturity that affect family stability. The article also addresses the development of criteria for personal maturity across various scientific and psychological approaches. It presents several theoretical perspectives on family and personal maturity and offers a comparative analysis of contemporary approaches.The study reveals that married individuals demonstrate a higher level of goal orientation, characterized by a stable, conscious, and consistent pursuit of desired outcomes. Goal orientation encompasses the ability to set objectives, plan their achievement, and overcome both internal and external obstacles. This trait is closely linked to the perception of life’s meaning and reflects an individual’s psychological maturity. Additionally, the research identifies lower levels of self-awareness among divorced participants. Since self-awareness—formed through reflection on one’s behavior and experiences—is a key indicator of personal maturity, its development may play a crucial role in maintaining family stability.Overall, the findings suggest that traits associated with personal maturity significantly influence the sustainability of marital relationships and can be further developed. These results open avenues for future research into the psychological factors that contribute to the preservation or dissolution of family bonds. The observed trends resulting from the study may indicate the presence of certain personal characteristics that can influence the stability of marital relationships.The research will contribute to the formation of approaches aimed at developing personal factors that support family stability.
Keywords: family; personal maturity; personal qualities; family stability; marital relations; comparative analysis